The nerdiest camping trip ever!. - Ochs, Susie
Technology and the great outdoors go together better than ever. Get out and geek out with these fun activities, apps, and gear!
Keywords: iPhone (Smartphone); iPad (Computer); Geocoaching; Wildlife Watching; Nerdy gear; Stargazing; Spot Connect; iGrill